Consensus of Clinical Neurorestorative Progress in Patients with Complete Chronic Spinal Cord Injury. Issue 1 (January 2014) - Huang, Hongyun; Sun, Tiansheng; Chen, Lin; Moviglia, Gustavo; Chernykh, Elena; Von Wild, Klaus; Deda, Haluk; Kang, Kyung-Sun; Kumar, Anand; Jeon, Sang Ryong; Zhang, Shaocheng; Brunelli, Giorgio; et al.
Currently, there is a lack of effective therapeutic methods to restore neurological function for chronic complete spinal cord injury (SCI) by conventional treatment. Neurorestorative strategies with positive preclinical results have been translated to the clinic, and some patients have gotten benefits and their quality of life has improved. These strategies include cell therapy, neurostimulation or neuromodulation, neuroprosthesis, neurotization or nerve bridging, and neurorehabilitation. The aim of this consensus by 31 experts from 20 countries is to show the objective evidence of clinical neurorestoration for chronic complete SCI by the mentioned neurorestorative strategies. Complete chronic SCI patients are no longer told, "nothing can be done." The clinical translation of more effective preclinical neurorestorative strategies should be encouraged as fast as possible in order to benefit patients with incurable CNS diseases. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation .